Gambaran Pasien Kanker Ovarium Tipe Epitel di RSUD Abdoel Wahab Sjahranie: Stadium, Usia, Status Menopause, dan Subtipe Histopatologis: Overview of Epithelial Ovarian Cancer Patients at Abdoel Wahab Sjahranie Regional Hospital: Stage, Age, Menopausal Status, and Histopathological Subtype - Della Ayu Lestari; Eva Rachmi; Andika Adi Saputra Achmad (ITKES Wiyata Husada Samarinda, 2025)
Ovarian cancer is the third most common gynecological cancer in women worldwide and has increased by 31.5% in 2020 compared to 2012, with the majority of cases being the epithelial type (90%). Ovarian cancer is one of the deadliest gynecological cancers because it tends to be asymptomatic or often has no clear symptoms so it can only be diagnosed at an advanced stage. This study describes the stage, age, menopausal status, and histopathological subtype in patients with epithelial ovarian cancer at Abdoel Wahab Sjahranie Hospital, Samarinda, which was conducted from August to December 2023. The design of this study was descriptive observational with a cross-sectional approach. The sampling technique was purposive sampling and based on secondary data in the form of medical records, totaling 30 patients. The highest proportion was found in stage III (50%). The age distribution was dominated by 41 – 60 year (56.67%), menopausal status was dominated by the postmenopausal group (73.33%), and the most common histopathological subtype was serous (63.33%).